Celebrating nationhood: Negotiating nationhood and history in Finland's centenary celebrations. Issue 4 (16th July 2020) - Sakki, Inari; Hakoköngäs, Eemeli
Abstract: National celebrations are one of the ways by which nations attempt to maintain connectedness with the past and strengthen national identities. Centenary celebrations, in particular, make identity questions visible and bring them to the centre of public debate and, thus, provide an opportunity to examine question such as 'where do we come from' and 'where are we going'. In this research, we examine conceptions of nationhood and history in the year of the Finnish centenary 2017. As the Finnish centenary programme was simultaneously organised 'from above' as an elite‐driven and 'from below' as citizen‐driven collective endeavour, it provided unique material for exploring the construction, meanings and negotiations of social representations of nationhood and history. Our analysis brings forth the power struggle of meanings, the ways in which hegemonic narratives are challenged and contested and the ways in which affects and emotions are entangled with the meaning‐making in commemoration and nation‐building practices, for example, by employing narrative empathy in commemorations. Different projects of the centenary programme make different subject positions available for the participants, such as a position of hardworking Finn or brave Finn in hegemonic narratives and, respectively, a position of emancipated women or fragile and traumatised soldiers in alternative narratives.